Critiques of Student Engagement. Issue 1 (March 2017) - Macfarlane, Bruce; Tomlinson, Michael
Abstract Student engagement initiatives at the national, institutional and classroom level have emerged against a backdrop of rising participation rates and the marketisation of higher education. This context has informed the development of a literature that is heavily influenced by cause-effect framing and a focus on effectiveness. However, in recent years an alternative, critical literature has emerged that challenges some of the assumptions of the student engagement movement on the grounds of student rights and freedoms as learners. This review article identifies the following six critiques of student engagement based on an analysis of the literature and arguments stemming from analyses of the effects of neoliberalism, namelyperformativity, marketing, infantilisation, surveillance, gamification andopposition . It is concluded that at a policy and institutional governance level, there is a need to shift the emphasis from what and how questions concerning student engagement to consider its broader political, economic and ethical implications as a means of challenging the prevailing policy narrative.